A biomechanical multibody foot model for forward dynamic analysis - Moreira, Pedro (2011)
The main goal of this work is to present a comprehensive three-dimensional biomechanical multibody foot model suitable to perform forward dynamic analysis. The proposed approach takes into accounts the different contact phenomena that develop between the foot and ground, namely the geometric, kinetic, dynamic and material properties of the foot-ground interface during the stance phase of the human gait. Furthermore, the system dynamics response during the swing phase is considered through the use of a linear torsional spring damper element. The biomechanical model used here consists of 3 rigid bodies, corresponding to the shank, main anatomical foot part and toes, which are connected by revolute joints. The anthropometric dimensions of the model correspond to those of a male of 1.70 m and 70 kg. This biomechanical system encompasses 6 functional degrees of freedom: 3 for the knee/shank translational trajectories, 1 for the knee flexion, 1 for the ankle joint rotation and 1 for the metatarsal-phalangeal joint rotation. The interaction between the foot and ground bodies is provided by the introduction of a set of spheres under the plantar surface of the foot. In the sequel of this process, a general mathematical methodology for contact detection between the foot and ground surfaces is presented. Then, in a simple way, when the foot-ground contact occurs, appropriate constitutive laws for contact phenomena are applied. These laws take into account the vertical ground reaction force as well as the friction phenomena, namely the Coulomb and viscoelastic friction effects. The proposed contact approach is able to compute not only the ground reactions forces but also to evaluate the position of the center of pressure under the foot plantar surface. Finally, the results obtained from computational and experimental analysis are used to discuss the main assumptions and procedures adopted through this work.